PUTUSAN MAHKAMAH AGUNG NO. 981K/PDT/2009 TERHADAP PEMBATALAN SERTIFIKAT HAK PAKAI NO. 765 ATAS NAMA PEMERINTAH KOTA MEDAN - EVI FITRIANI (PREMISE LAW JURNAL, 2015)
The ownership of the Right of Use No. 765/Pusat Pasar certificate on behalf of Medan City Administration on July 1, 1996 which was legally given by the Land Office of Medan could be cancelled by the claim of Hin An Hui Association (Perhimpunan) in 2007, based the Ruling of the Supreme Court No. 981K/Pdt/2009. The research was descriptive analytic with judicial normative approach.The data were gathered by using library research and analyzed qualitatively. The conclusions of the research were as follows: 1) the factors which cancelled the certificate were a) the Association was legally established according to the prevaling law, b) the Association could give evidence about the grounds of its claim, and c) the ceding land rights had proved that the Association had controlled and used the disputable object based on the sales agreement on February 12, 1957, 2) The reason of the cancellation of the certificate, based on the Ruling of the Supreme Court, was legal since it was not contrary to law, and 3) legal protection for Medan City Administration  was by cancelling all verdicts of Medan District Court, Medan Higher Court, and the Supreme Court. Keywords: Cancellation, Certificate, Rights of Use, Land Registration